Persepsi keselamatan pelancong di kawasan ekopelancongan kajian kes: Taman Negara, Pahang - Ismail, Nurul Iswani (2006)
Perception of safety among tourists is an important aspect in forming an image of a destination. A negative perception may destroy the destination’s image. Numerous studies have been conducted in the urban areas regarding safety, however, there is only a few that is carried out in an ecotourism destination. This study is aimed to evaluate tourists’ perceptions towards safety in an ecotourism destination, which is Taman Negara Pahang. Safety aspects that is studied comprise of tourists’ perceptions while sightseeing during the day-time, engaging in activities, using transports to Taman Negara, utilizing facilities provided and walking at night. The study has found that tourists felt unsafe while walking in the outdoors at night and while kayaking. Tourists’ perceptions on safety are also identified whether it has any correlation with the tourists’ socio-demographic factors. The findings has concluded that factors of age, travel mode and frequency of visiting Taman Negara is very closely related to tourists’ perceptions towards their safety in Taman Negara. Other than socio-demographic factors, tourists’ perceptions on safety are also correlated with level of visitor management towards safety management in Taman Negara